Human Papillomaviruses and Epstein–Barr Virus Interactions in Colorectal Cancer: A Brief Review - Queenie Fernandes (14557388) (2020)
Human papillomaviruses (HPVs) and the Epstein–Barr virus (EBV) are the most common oncoviruses, contributing to approximately 10%–15% of all malignancies. Oncoproteins of high-risk HPVs (E5 and E6/E7), as well as EBV (LMP1, LMP2A and EBNA1), play a principal role in the onset and progression of several human carcinomas, including head and neck, cervical and colorectal. Oncoproteins of high-risk HPVs and EBV can cooperate to initiate and/or enhance epithelial-mesenchymal transition (EMT) events, which represents one of the hallmarks of cancer progression and metastasis. Although the role of these oncoviruses in several cancers is well established, their role in the pathogenesis of colorectal cancer is still nascent. This review presents an overview of the most recent advances related to the presence and role of high-risk HPVs and EBV in colorectal cancer, with an emphasis on their cooperation in colorectal carcinogenesis. Other Information Published in: Pathogens License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.3390/pathogens9040300